2021
DOI: 10.15252/emmm.202114323
|View full text |Cite
|
Sign up to set email alerts
|

Very‐low‐carbohydrate diet enhances human T‐cell immunity through immunometabolic reprogramming

Abstract: Very‐low‐carbohydrate diet triggers the endogenous production of ketone bodies as alternative energy substrates. There are as yet unproven assumptions that ketone bodies positively affect human immunity. We have investigated this topic in an in vitro model using primary human T cells and in an immuno‐nutritional intervention study enrolling healthy volunteers. We show that ketone bodies profoundly impact human T‐cell responses. CD4+, CD8+, and regulatory T‐cell capacity were markedly enhanced, and T memory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 82 publications
(87 reference statements)
5
50
0
Order By: Relevance
“…Patient characteristics are depicted in Table 1 . Lymphocytes were subjected to an established cell culture model ( 8 ) and cultivated with D/L-BHB (BHB + ) under T-cell specific stimulation (CD3/CD28 dynabeads, Supplementary Figures 1A–D ). These cells will be referred to as BHB + CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics are depicted in Table 1 . Lymphocytes were subjected to an established cell culture model ( 8 ) and cultivated with D/L-BHB (BHB + ) under T-cell specific stimulation (CD3/CD28 dynabeads, Supplementary Figures 1A–D ). These cells will be referred to as BHB + CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that BHB boosters CD8 + T-cell function by inducing significantly higher expression of central immune cytokines and enhanced cytotoxicity. These changes were based on a substantial rewiring of T-cell immunometabolism toward mitochondrial oxidative energy production ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hirschberger et al ( 2021) studied the effect of a very low-carbohydrate diet on T cell immunity in an in vitro model on human T cells and in a study in healthy volunteers. According to the results of the study, the authors demonstrated that ketone bodies formed during a very low-carbohydrate diet enhance the response of CD4+ and CD8+ cells [73]. A review by Cadler (2021) provides information suggesting that both obesity and malnutrition hurt the immune response to COVID-19 and may be factors contributing to the severe course of the disease [74].…”
Section: Other Peculiaritiesmentioning
confidence: 99%
“…Conversely, isocaloric ketogenic diets consisting of high fat (70–80%) and low carbohydrate (5–10%) content increase naïve T cell fatty acid oxidation, promoting Treg differentiation and IL-10 production ( 64 ). To our knowledge, only one study has investigated the impact of a ketogenic diet over 3 weeks on Treg induction in humans ( 64 ). Data in mice are inconsistent depending on the model with either an increase in Tregs in a carcinomatous peritonitis model ( 65 ) or a decrease in a diabetic obese mouse ( 66 ).…”
Section: Impact Of Diet On Treg Developmentmentioning
confidence: 99%
“…Conversely, isocaloric ketogenic diets consisting of high fat (70–80%) and low carbohydrate (5–10%) content increase naïve T cell fatty acid oxidation, promoting Treg differentiation and IL-10 production ( 64 ). To our knowledge, only one study has investigated the impact of a ketogenic diet over 3 weeks on Treg induction in humans ( 64 ).…”
Section: Impact Of Diet On Treg Developmentmentioning
confidence: 99%